Design of Dynamic Routing Scheme in Telecommunication Networks - Hailan, Ahmad M.; Tariki, N.; Vavenko, T.V. (My University, 2015)
In this paper the dynamic routing model of TCN is proposed. The novelty is that it is presented as a system of linear differential equations to describe the process of redistribution capacities of links and nonlinear algebraic equations to describe the routing of flows and congestion control. Using this model gives the opportunity to provide more efficient management of TCN resources when multiservice traffic is serviced.
Keywords: Dynamic routing; Quality of Service; Flow; Multiservice traffic; Prediction period